Missing you already - Code Red; Graham, Nicky; Telstar Records; Avex Trax. (London : Telstar Records, 1999)
Contains fifteen pop tracks, with an interview recording and a message from the artists to fans.
CD 1 : What Would You Do, If? -- What Good Is A Heart -- Everytime You Go Away (exclusive bonus track) -- Missin' You Already -- Guess I'm Lost In You -- Soothe Me -- Don't Go There -- Just A Little More -- Take My Heart -- Everybody Raise Your Hands -- When I Close My Eyes -- The Girl I Used To Know -- Alone With U -- What Would You Do, If? (garage mix) -- What Good Is A Heart (smooth vibe mix) -- Interview -- Message To Fans.
Koleksi Khas Wiramanja.
Group members : Phil Rodell, Neil Watts, Lee Missen, Roger Ratajczak.
Title from disc label.
Keywords: Songs, English